Administrative Impacts of ETS2 Emissions Trading on Regulated Entities in Finland - Syrjä, Silja (2025)
This thesis examines the administrative impacts of the emissions trading system for fuels (ETS2) on regulated entities. The research applies a mixed methods approach, combining quantitative descriptive analysis with qualitative thematic analysis. Data was collected through an online questionnaire, with responses received from 34 regulated entities. The aim was to find out what challenges companies face in complying with the administrative obligations of ETS2 and how they are preparing for the regulatory change. The results show that especially smaller entities perceive the regulation as burdensome. However, unclear guidance, time pressure, and resource constraints were broadly reported across company sizes. Levels of preparedness varied significantly, and some respondents felt the regulation was disproportionate to their business scale. The results are analyzed through Kurt Lewin’s three-phase model of organizational change.